PERSONALITY STRUCTURE OF THE MAIN CHARACTERS IN KATHRYN STOCKETT’S HISTORICAL FICTION "THE HELP" - Ardhani, Della (Journal of Language, Literature and Teaching, 2025)
This article aims to analyze the personality structures of the three main characters in the novel "The Help" by Kathryn Stockett namely Aibileen Clark, Minny Jackson, and Eugenia “Skeeter” using Carl Rogers' humanistic personality theory which include three concepts; self, organism, and phenomenal field, which together form the foundation of individual personality development and self-perception.The research adopts a descriptive-qualitative method with a literary psychology approach, examining the psychological aspects of each character as portrayed in the novel. Data were collected through close reading and interpretation of the characters’ thoughts, behaviors, and experiences, then categorized based on Rogers’ theoretical concepts to reveal patterns of personality structure and development.The findings show that all three characters display unique and complex personality structures, shaped by their personal experiences, social roles, and internal conflicts. The study concludes that Carl Rogers’ theory is highly effective for uncovering the psychological depth of literary characters and understanding how they grow through internal and external challenges.